(untitled) (International Journal of Engineering and Computer Science, 2015)
This survey paper consists of various image processing techniques used for the detection of the salient region. The paper also includes the comparative study of these techniques like precession recall analysis and the relative advantages and disadvantages. The major topic of our interest is the Salient Region of the object which is an important factor in most of the areas like cognitive psychology and neurobiology. The various technique are different in there logic and performance the involved. Comparing to all the techniques on there both positive and negative sides the paper presented here is the best in my behalf to its domain knowledge